Determinants of severe QTc prolongation in a real-world gerontopsychiatric setting - Schulze Westhoff, Martin; Schröder, Sebastian; Heck, Johannes; Pfister, Tabea; Jahn, Kirsten; Krause, Olaf; Wedegärtner, Felix; Bleich, Stefan; Kahl, Kai G.; Krüger, Tillmann H. C.; Groh, Adrian (Frontiers in Psychiatry, 2023)
Introduction QTc prolongation carries the risk of ventricular tachyarrhythmia (Torsades de Pointes) and sudden cardiac death. Psychotropic drugs can affect ventricular repolarization and thus prolong the QTc interval. The present study sought to investigate the risk factors (pharmacological and non-pharmacological) of severe QTc prolongation in gerontopsychiatric patients. Methods Electrocardiograms of patients on a gerontopsychiatric ward were screened for QTc prolongation. Medication lists were examined utilizing the AzCERT classification. Potential drug interactions were identified with the electronic drug interaction program mediQ. Results The overall prevalence of QTc prolongation was 13.6%, with 1.9% displaying severe QTc prolongation (≥ 500 ms). No statistically significant differences between patients with moderate and severe QTc prolongation were identified; however, patients with severe QTc prolongation tended to take more drugs (p = 0.063). 92.7% of patients with QTc prolongation took at least one AzCERT-listed drug, most frequently risperidone and pantoprazole. Risperidone and pantoprazole, along with pipamperone, were also most frequently involved in potential drug interactions. All patients displayed additional risk factors for QTc prolongation, particularly cardiac diseases. Conclusion In addition to the use of potentially QTc-prolonging drugs, other risk factors, especially cardiac diseases, appear to be relevant for the development of QTc prolongation in gerontopsychiatric patients. Pantoprazole was frequently involved in potential drug interactions and should generally not be used for more than 8 weeks in geriatric populations. As clinical consequences of QTc prolongation were rare, potentially QTc-prolonging drugs should not be used overcautiously; their therapeutic benefit should be considered as well. It is paramount to perform diligent benefit–risk analyses prior to the initiation of potentially QTc-prolonging drugs and to closely monitor their clinical (side) effects.